Removal (and attempted removal) of material from a Hooded Vulture Necrosyrtes monachus nest by a starling and a Hooded Vulture§. (31st August 2017) - Thompson, Lindy J; Davies, John P; Bildstein, Keith L; Downs, Colleen T
Abstract : Relatively little is documented about nest material theft in vultures. We used camera traps to monitor Hooded Vulture Necrosyrtes monachus nests for a year. We report camera trap photographs of a starling Lamprotornis sp. removing what appeared to be dung from an inactive Hooded Vulture nest on Cleveland Game Reserve, north-eastern South Africa, in October 2016. We also had evidence of a Hooded Vulture attempting to remove twigs from the same nest in August 2016. This behaviour is previously unrecorded in Hooded Vultures and, although seemingly rare, it represents an attempt to reduce the energetic costs of nest building in this species.